Досвід формування професійної компетентності майбутніх учителів історії в Глухівському учительському інституті у 1874–1917 роках - Курок, О.І.; Гриценко, А.П. (Сіверщина в історії України, 2020)
Авторами статті проаналізовано історію розвитку Глухівського учительського інституту з часу його створення і до 1917 року через призму методичної діяльності його викладачів та студентів. У ході розгляду даного питання представлено досвід формування професійної компетентності майбутніх учителів історії, що навчались у виші. Звернено увагу на те, що в учительському інституті упроваджувалися передові методики того часу з формування предметно-історичних компетентностей, які актуальні й нині. На прикладах підтверджено необхідність розвитку у майбутніх учителів історії загальнопедагогічних умінь і навичок, що включають педагогічне спілкування, уміння здійснювати контроль, навички самостійної роботи та здатність до педагогічної творчості й імпровізації, а також потребу у професійно-педагогічному самовдосконаленні. The author of the article analyzed the history of the development of the Hlukhiv Teachers’ Institute from the time of its creation until 1917 through the lens of methodical activity of its teachers and students of the institution. In the course of consideration of this issue the experience of forming the professional competence of future history teachers studying in higher education is presented. Attention is drawn to the fact that the teaching methods of the time were introduced at the Teachers’ Institute of that time in the formation of subject-historical competences, which are still relevant today. The Hlukhiv Teacher Training Institute was a closed educational institution with a three-year term of study, where general and Russian history were relevant to compulsory subjects. Since the early years, much attention has been paid to organizing the educational process, introducing new achievements in psychology and pedagogy, studying and generalizing the experience of the best teachers of public schools. There were active methodological and scientific work among teachers and students at the Institute. It was significantly enriched in the early twentieth century. advanced pedagogical theory and practice of formation of future teachers of professional competence. It is considered to be a set of knowledge, skills, personal qualities of a future specialist, necessary to ensure effective professional activity, including interconnected structural components. Methodical work at the Hlukhiv Teacher’s Institute included the formation of all components of subject-historical competence. The examples confirmed the need for future teachers to develop a history of general pedagogical skills, including pedagogical communication, the ability to exercise control, independent work skills and the ability for pedagogical creativity and improvisation, as well as the need for professional pedagogical training.